Transcriptional profile of a bioethanol production contaminant Candida tropicalis - Lourencetti, Natália Manuela Strohmayer [UNESP]; Wolf, Ivan Rodrigo [UNESP]; Lacerda, Maria Priscila Franco [UNESP]; Valente, Guilherme Targino [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Santoni, Mariana Marchi [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Enguita, Francisco Javier; Fusco-Almeida, Ana Marisa [UNESP] (Springer Nature, 2018)
The fermentation process is widely used in the industry for bioethanol production. Even though it is widely used, microbial contamination is unpredictable and difficult to control. The problem of reduced productivity is directly linked to competition for nutrients during contamination. Yeasts representing the Candida species are frequently isolated contaminants. Elucidating the behavior of a contaminant during the fermentation cycle is essential for combatting the contamination. Consequently, the aim of the current study was to better understand the functional and transcriptional behavior of a contaminating yeast Candida tropicalis. We used a global RNA sequencing approach (RNA-seq/MiSeq) to analyze gene expression. Genes with significantly repressed or induced expression, and related to the fermentations process, such as sugar transport, pyruvate decarboxylase, amino acid metabolism, membrane, tolerance to high concentrations of ethanol and temperatures, nutrient suppression), and transcription-linked processes, were identified. The expression pattern suggested that the functional and transcriptional behavior of the contaminating yeast during fermentation for bioethanol production is similar to that of the standard yeast Saccharomyces cerevisiae. In addition, the analysis confirmed that C. tropicalis is an important contaminant of the alcoholic fermentation process, generating bioethanol and viability through its tolerance to all the adversities of a fermentation process essential for the production of bioethanol. According on the gene expression profile, many of these mechanisms are similar to those of S. cerevisiae strains currently used for bioethanol production. These mechanisms can inform studies on antimicrobials, to combat yeast contamination during industrial bioethanol production.
Keywords: Alcoholic fermentation; Bioethanol; Candida tropicalis; Contaminant; RNA-seq